The Protestant Ethic and African Pentecostalism: A Case Study - Gifford, Paul; Nogueira-Godsey, Trad (Journal for the Study of Religion, 2011)
In 2008 South Africa's Centre for Development and Enterprise (CDE) produced a report on Pentecostalism, Under the Radar: Pentecostalism in South Africa and its Potential Social and Economic Role, which makes great claims for the public effects of Pentecostalism, proposing that Pentecostalism will do for South Africa what Max Weber argued Calvinism did for eighteenth-century Europe. The report is influenced by "the claims of sociologists of religion that Pentecostalism has a special affinity with market-based development, and a kinship with what historians call the 'Protestant ethic': a cluster of beliefs, attitudes and habits that underpinned the spectacular economic growth of north-west Europe during the industrial revolution." This article will review the results published by the CDE vis-à-vis the construction of a "Pentecostal Ethic" and present a case study of an African Pentecostal church, Winners' Chapel, which challenges the assertions made by the CDE. As an example of the prevalence of "victorious living" within African Pentecostalism, Winners' Chapel does not conform to the Weberian model of the Protestant Ethic.
free